Concurrent Atlantoaxial Septic Arthritis and Septic Thrombosis of the Ophthalmic Vein due to Staphylococcus aureus: A Case Report and Review of the Literature. (6th December 2018) - Hajar, Zeina; Fotedar, Neel; Jump, Robin L P
Abstract: Atlantoaxial joint septic arthritis and superior ophthalmic vein thrombosis are uncommon manifestations of Staphylococcus aureus infection. A 68-year-old man presented with acute-onset neck pain and diplopia. Imaging studies revealed atlantoaxial septic arthritis and right superior ophthalmic vein thrombosis. Blood cultures grew methicillin-susceptible S. aureus . We review the literature describing these 2 uncommon manifestations of a common pathogen.